Spontaneous obturator internus muscle haematoma: a new unpublished cause of ilioipelvic pain in haemophilia. (14th August 2012) - Aouba, A.; Breton, S.; Harroche, A.; Sy‐Bah, D.; Torchet, M.‐F.; Frenzel, L.; Lasne, D.; Padovani, J.‐P.; Odent, T.; Rothschild, C.
Summary Obturator muscles haematoma are rarely reported. The most often reported cases are primary pyomyositis or posttraumatic haematomas occurring during pelvic fractures. We firstly report herein two cases of spontaneous obturator internus haematoma (OIH) in two haemophiliacs with inhibitor. Clinical data and imaging of two patients treated in our clinic are reported here according to previously defined criteria of OIH in posttraumatic situation. Both patients were children suffering from severe and moderate haemophilia A, respectively, with an inhibitor at the time of the event. The clinical feature was marked by an iliopelvic pain letting discussing hip haemarthrosis, appendicitis or iliopsoas haematoma. For both patients ultrasonography (US) failed to provide the diagnosis. Careful and repeated clinical examinations eventually lead to suspect obturator haematoma which was confirmed by abdominopelvic computed tomography (CT) and magnetic resonance imaging (MRI). Respectively, high dose of FVIII or rFVIIa regimen allowed a rapid control of the muscular bleeding in the low and high responder inhibitor patients. Spontaneous OIH may be added to the differential diagnosis of iliopelvic pain in severe forms of haemophilia. US still often performed at first in such case remains unhelpful; abdominopelvic CT or MRI should be performed to discriminate among different diagnoses, including OIH which stays probably undiagnosed.